العالقة االنعكاسية بين الدين والسياسة  دراسة في جذورها وطبيعتها - سردار قادر محى الدين; مهدي أبوبكر حمە عەلی (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Despite differentiations of religious and political natures, they always interevent with values that is main thing that both religion and politics are focused on. When the religion teaches individuals a certain value, the life of individuals in society will be monopolized by that value. At the same time, politics determine the society’s values and make binding decisions concerning those values. The individual is unable violate those binding decisions that control their lives in society. The values that religion establishing in life of individuals and society may turn into official values in the political system. Religious opinions and values may also be a source of values adopted by the political system. Moreover, religion always influences multiple ways in the values of society and seeks expression and implementing of values through the state authority. This often leads to the entry of religion in conflicts for the sovereignty of its values in society. Consequently, values are the main issue that attaches religion to politics, and this is the initial point for the beginning of the reflexive relationship between them. To the extent that the relationship between religion and politics is focused on in the three monotheistic religions and although it has passed through many stages, it remains strong until nowadays. These three religions can influence political systems in various means. In contrast, political regimes have not been silent concerning utilizing religion as a means of guaranteeing their legitimacy.